Scaling of low-temperature conductivity spectra of BaSn 1xNbx: Temperature and compositional-independent conductivity - Singh P.; Raghvendra; Parkash O.; Kumar D. (My University, 2025)
We report our investigation on the low temperature scaling behavior of niobium-doped barium stannate. Electrical properties of the system BaSn 1-xNbxO3 (with x=0.001, 0.005, 0.010, 0.050, and 0.100), prepared by the solid-state route, were studied employing impedance spectroscopy in the temperature range 123-273 K and frequency range 10 -2 Hz to 3 MHz. Conductivity spectra for all the compositions were found to follow Jonscher's power law, σ′= σdc[1+(ν/νH )p]. We found that the hopping frequency νH, obtained from fitting this equation to the conductivity spectra, can be used as a scaling factor. All the compositions follow the time-temperature-superposition principle, with νH as the scaling frequency. Moreover, the conductivity spectra of compositions with x ≤ 0.010 and with 0.010 < x ≤ 0.100 were separately found to show compositional scaling behavior with respect to the hopping frequency νH. This system showed a change in the charge compensation mechanism from electronic to ionic in its temperature dependence of the dc conductivity as the concentration changed from x=0.010 to x=0.050. The shape of the conductivity spectra also changed as the concentration changes from x=0.010 to x=0.050. We conclude that in this system, when the conduction mechanism does not change, νH can be used as a universal scaling parameter. © 2011 American Physical Society.